FAKIH: A method to teach deaf people ‘reading’ Quran - Mohd Daud, N.A.; Jomhari, N.; Abdull Zubi, N.I. (2012)
Allah revealed the Quran to be practiced by all human beings irrespective of whether the humans are normal, or mentally or physically challenged. According to the Department of Malaysian Special Education, in 2002, there were 663 blind students and 3649 deaf students, all over Malaysia. However, in terms of Quran education, deaf students are far behind compared to blind students. This is because they could not hear and therefore posed a difficult situation for the teachers to teach them. Based on this initiative, Fakih methods have been introduced to eight deaf students to learn Quran in within two months. The result is very promising where six of them managed to recite Quran through hand code using Fakih method. We propose iPad application called iFakih in the future to cater the needs of disabled people to read Quran.